PENGARUH LATIHAN SMALL SIDED GAME TERHADAP AKURASI PASSING PADA SISWA EKSTRAKULIKULER FUTSAL SMP NEGERI 1 MUARO JAMBI - Ahmad Muzaffar; Adhe Saputra (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2019)
Small sided-games training is a small-scale field, an appropriate situation developed for young players, so they can learn and develop. Small sided games training is also one of the methods of soccer training using smaller fields with fewer players. This training method is a fairly effective exercise in physical improvement, techniques and tactics Passing is to feed the ball or pass the ball to a friend, while passing determination is the ability to set goals / pass the ball according to the goal or target. This research is an experimental research conducted with the aim to find out whether or not there is a result of something done on the sample to be studied. The research began with a pretest and ended with a posttest. The number of samples in this study amounted to 20 people. The training given was done during 16 meetings. This research was tested using a statistical analysis of the hipotsis test (t test). Based on data analysis, it can be concluded that the small sided games exercise gives a significant effect on the accuracy of passing on extracurricular students at SMP Negeri 1 Muaro Jambi, proven in the pre-test and post-test assessments with an average pre-test = 505 and post-test = 7.65, with the increment difference of 7.65. This can be seen by the T test that is Tcount = 3.492787 Ëƒ Ttable = 1.72913. Based on the results of research and calculations from the data and discussions that have been carried out, this research proves that there is an influence of small sided games training on the passing accuracy of extracurricular students at Muaro Jambi State Junior High School. Small sided-games training is a small-scale field, an appropriate situation developed for young players, so they can learn and develop. Small sided games training is also one of the methods of soccer training using smaller fields with fewer players. This training method is a fairly effective exercise in physical improvement, techniques and tactics Passing is to feed the ball or pass the ball to a friend, while passing determination is the ability to set goals / pass the ball according to the goal or target. This research is an experimental research conducted with the aim to find out whether or not there is a result of something done on the sample to be studied. The research began with a pretest and ended with a posttest. The number of samples in this study amounted to 20 people. The training given was done during 16 meetings. This research was tested using a statistical analysis of the hipotsis test (t test). Based on data analysis, it can be concluded that the small sided games exercise gives a significant effect on the accuracy of passing on extracurricular students at SMP Negeri 1 Muaro Jambi, proven in the pre-test and post-test assessments with an average pre-test = 505 and post-test = 7.65, with the increment difference of 7.65. This can be seen by the T test that is Tcount = 3.492787 Ëƒ Ttable = 1.72913. Based on the results of research and calculations from the data and discussions that have been carried out, this research proves that there is an influence of small sided games training on the passing accuracy of extracurricular students at Muaro Jambi State Junior High School.